Detecção precoce dos transtornos invasivos do desenvolvimento: atuação do enfermeiro - Braga, Maria Rita (2011)
Early identification of Pervasive Developmental Disorders (PDDs) is important for a better prognosis on affected children. Therefore, the position stood by nurses performing in the primary health care, is relevant to identify the characteristic signs of these disorders. The objectives of this study were to subsidize the nurses´ knowledge by empowering them to detect earlier the Pervasive Developmental Disorders, and to verify this empowerment repercussion into their performance on surveillance of childhood development. Afterwards, to evaluate the program adjustment into this empowerment, according to the perception of these nurses intervention-participants. Method: An almost-experimental outline featured by a teaching intervention was used. The participants were divided according to their availability into two groups: an experimental group (EG received intervention), and a control group (CG did not receive the intervention). The casuistic comprised 27 nurses from the Primary Health Care Units (PHCUs), in a municipality of São Paulo state, with attendance in Puericulture. Data collection was made by semi-structured interview, during three distinctive phases: pre-intervention, post-intervention and follow-up. During the pre-intervention and follow-up phases, data were also collected from the children’s parents (n=83 and 79, respectively). Results: Data analysis allowed to observe that after participating the course, the nurses of the EG demonstrated to have acquired new knowledge on the theme; otherwise, the nurses of the CG did not. However, significant changes on these nurses´ acting regarding the surveillance of the children´s development were not observed. It is important to consider the influence of the organizational framework in changing the process of health assistance model. Regarding the empowerment program, the nurses, were satisfied in relation to all assessed aspects, suggesting to spread this empowerment to other professionals. Conclusions: The results allowed to conclude that the course program was feasible, and the implemented empowerment has provided important contributions on the surveillance of the children´s development, and early detection of the Pervasive Developmental Disorders. Moreover, further research should be carried out to optimize some action implementation aiming to identify these disorders and to support a better future for these children and their family.